Determinan Inflasi: Pendekatan Al-Maqrizi dan Perspektif Manajemen Syariah - Salman Al Parisi (Islamic Economics Journal, 2018)
Inflation is one of problem in economy. Data BPS from January 2010 until December 2017, explained that average inflation in Indonesia showed a high trend at 5.24 percent. This paper uses Multiple Linear Regression Model. This paper tried to analyze the influence of human error inflation (corruption, money supply and the excess of tax rate) on inflation in Indonesia. The result showed that LNMoney Supply has significant positive effect on inflation rate at alpha 5%, ceteris paribus. Control of corruption has signifikan negative effect on inflation rate at alpha 1%, ceteris paribus. Then, LNtax has significant positive effect on inflation rate at alpha 1%, ceteris paribus. Therefore Islam and Al-Maqrizi prohibit the corruption practices and the use of interest rates as an instrument of government policy.